Compliance with vaccination against tick-borne encephalitis virus in Germany. (July 2017) - Jacob, L.; Kostev, K.
Abstract: Objectives: The goal of this study was to analyse patients' compliance with vaccination against tick-borne encephalitis (TBE) virus in Germany. Methods: The present study included 7266 patients from 638 general practices and 4194 patients from 114 paediatric practices. Patients were included if they had received the first dose of one of two vaccines against TBE virus (FSME-Immune ® and Encepur ® ). The immunization schedule of these vaccines consisted of three injections. Patients were considered compliant if they received the second and third doses at the recommended time or within a period of ±25% around the recommended time (tolerance period). Results: Of the recruited patients, 28% received both the second and the third injections within the tolerance period. Individuals treated in paediatric practices had a higher likelihood of receiving vaccine doses within the tolerance period compared with individuals treated in general practices (OR 2.15; 95% CI 1.92–2.41). Moreover, patients <18 years old were more likely to be compliant than patients >65 years old (OR 1.22; 95% CI 1.02–1.46), whereas patients aged between 18 and 30 years were least likely to be compliant (OR 0·77; 95% CI 0.61–0.96). Conclusions: Compliance with vaccination against the TBE virus was low. This compliance was significantly associated with age and the type of practices in which patients were treated.